Development and Validation of Stability indicating liquid chromatography method for the simultaneous quantification of Remogliflozin Etabonate, Vildagliptin and Metformin in combined formulation dosage forms (International Journal of Food and Nutritional Sciences, 2022)
The fixed dose combination of remogliflozin etabonate, vildagliptin and metformin was recently approved for the treatment of type 2 diabetes and can improve glycemic control in patients. In the literature, there is no HPLC method reported for the estimation of remogliflozin etabonate, vildagliptin and metformin and hence the present study was aimed to develop a simple stability indicating HPLC method for the quantification of these analytes in combined dosage forms. The optimized and best separation was achieved using Phenomenex Luna C18 (250 mm × 4.6 mm, 5 μm) as stationary phase, pH 5.2 acetate buffer and acetonitrile in 55:45 (v/v) as mobile phase at 1.0 mL/min and PDA detection at 218 nm. The method reported a sensitive detection limit of 0.375 µg/mL, 1.875 µg/mL and 0.188 µg/mL with linearity range of 5-30 µg/mL, 25-150 µg/mL and 2.5-15 µg/mL respectively for remogliflozin, vildagliptin and metformin. The method passes all the validation parameters as per the guidelines proved that the method was valid. The method can shows very less % degradation in various stress studies such as acidic, base, peroxide, thermal and UV light conditions and can effectively separate various stress degradation compounds confirms the stability indicating nature of the method. The method can adequately suitable for the separation and quantification remogliflozin, vildagliptin and metformin in formulation hence can be applicable for the routine analysis of remogliflozin, vildagliptin and metformin in pharmaceutical dosage forms.